"If the Workers Took a Notion": The Right to Strike and American Political Development - Cantin, Étienne (Relations industrielles / Industrial Relations, 2007)
The article reviews the book, "If the Workers Took a Notion: The Right to Strike and American Political Development," by Josiah B. Lambert.
Keywords: American history; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strikes